IMPLEMENTATION OF A JUDGE'S DECISION REGARDING THE EVIDENCE STATUS IN CRIMINAL CASES RELATED TO BANKRUPTCY CONFISCATION - Rusmiati, Elis (Jurnal Bina Mulia Hukum, 2023)
This article discusses criminal acts with the characteristics of a large number of victims and losses, one of which is the case of PT First Travel and Abu Tour with the same motive and article being charged. For the purposes of examining criminal cases since the preliminary examination stage, the process of confiscating evidence has been carried out, including goods which are the object of a crime, proceeds of a crime and other goods related to a crime, including goods in bankruptcy confiscation. The issues discussed are the application of the status of evidence in criminal cases related to bankruptcy confiscated goods in a judge's decision and efforts to return evidence in meeting the victim's loss due to a crime. Using the normative juridical research method, it was concluded that the consideration of judges, which is one of the most important aspects in determining the realization of the value of a judge's decision, was not carried out carefully and thoroughly, one of which was in decisions 3096 K/Pid.Sus/2018 and 3127 K/PID.SUS/2019 which makes no sense at all. Efforts are needed to return the confiscated evidence from the victim to overcome the losses suffered, in several ways, namely improving the search and filing administration system for evidence subject to confiscation from the investigation stage so that the case files at the prosecutor's office are included if there is already a bankruptcy confiscation.